Analisis Manajemen Strategik pada Megah Supplier Catering - Pratama, Achmad Ryan Hadi; Wisnucahyo, Arya Senna; Antani, Puan; Lutfi, Yudhi; Tiarapuspa (STIE Widya Manggala, 2024)
This research is a type of qualitative field research. Primary data was obtained from the results of in-depth interview with competent informants. Secondary data is documents, reports, books, research journals and articles that are still related to research problems. The method used is Internal Factor Evalution (IFE), Eksternal Factor Evaluation (EFE), Strength, Weakness, Opportunities, Threats (SWOT), and interviews. The results of the research slow that in the IFE Matrix the strength and weakness factors have a total score of (2), this identifies that Megah Supplier Catering is in a strong internal supplier position, where this business has good strengths in termas of partnering with major raw material suppliers. Then in the EFE Matrix analyzes that Megah Supplier Catering has opportunities and threats with a weigth score of (1,89). This identifies that Megah Supplier Catering’s efforts to suppress strength with SWOT strategy opportunities, it is obtained to maintain a good taste and strategic location in Jakarta City Center.